Asymmetric intramolecular Friedel–Crafts reaction catalyzed by a spiropyrrolidine organocatalyst: Enantioselective construction of indolizine and azepine frameworks. Issue 45 (7th November 2018) - Zhang, Yi-Hang; Yuan, Yong-Hai; Zhang, Shu-Yu; Tu, Yong-Qiang; Tian, Jin-Miao
Graphical abstract: Highlight: Asymmetric Friedel-Crafts reaction using our SPD-type organocatalyst. Construction of azepine and indolizine frameworks in excellent ee. All-carbon quaternary center in indolizine frameworks was generated. Abstract: The asymmetric intramolecular Friedel–Crafts type Michael reaction of α, β-unsaturated aldehyde with pyrrole, catalyzed by a spiropyrrolidine (SP)-type organocatalyst, has been accomplished, which allows the construction of a series of azepine and indolizine frameworks with high to excellent enantioselectivities (up to 98% ee). Moreover, the substrate scope could be extended to generate a quaternary center in indolizine frameworks (up to 96% ee).